Computer Aided Design and Analysis in Die/Mould of Casting Process - Abedin, Md. Shamsul (1997)
Computer Aided Design (CAD) and Computer Aided Analysis (CAA) have been investigated and developed since the last twenty years as standalone systems. There is useful link between CAD and CAA in terms of data extraction from the graphics to non-graphics format for the analysis. Computer Aided Design and Computer Aided Analysis packages have been developed incorporating AutoCAD for the fluid feeding progress and the thermal behaviour during the casting process. Network analysis process has been adopted for the current development. The Developed package includes the CAD graphics for design, transferring graphics to non-graphics and vice versa for pre-processing and post-processing for the Engineering Analysis. The Developed package has been tested for the Die/Mould design for the proposed model. Finite element packages have been used for the prediction of the residual stresses of the Die/Mould.